STRUKTUR CERITA RAKYAT JAWA TENGAH BALAI-BALAI KAYU JATI: KAJIAN ANTROPOLOGI SASTRA - Nailatunnajah, Nailatunnajah; Yundiani, Sri; Khumairoh, Viny; Amelia, Zahra (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2024)
Folklore is a story passed down from generation to generation that has been passed down from generation to generation orally to be preserved. Folklore contains aspects relating to attitudes, behavior and cultural values of society. Literary anthropology studies discuss literary works by emphasizing cultural values. This research aims to explain the structure and content of the story of Balai-Balai Kayu Jati and reveal the cultural reflection of Central Javanese society (especially the Tlogosari community). Balai-Balai Kayu Jati are analyzed from two perspectives, namely as works of fiction and as physical evidence of culture. As a work of fiction, a study is carried out on the structural elements of the story, while as physical evidence of culture, it is analyzed using a literary anthropology approach. The research results show that structurally, the story of Balai-Balai Kayu Jati is composed of characters, themes, settings and story points of view. Meanwhile, by using a literary anthropology approach, we can understand the cultural side of the people of Tlogosari, Central Java, namely the aspects of knowledge, technology, social society and art.